The benefits and limitations of a genre - based approach to teaching writing to grade 10 students in Tan Trao high schoool, Tuyen Quang province = Những lợi ích và hạn chế của đường hướng dựa vào thể loại đối với việc dạy viết cho học sinh lớp 10 trường T - Bùi, Thị Thu Huyền (University of Languages and International Studies, 2017)
42 p. + CD-ROM